VARIASI DIAMETER ZEOLIT UNTUK MENURUNKAN KADAR BESI (Fe) PADA AIR SUMUR GALI (Studi Kasus Pada Sumur Gali Desa Lodoyong Kecamatan Ambarawa Kabupaten Semarang) - Khimayah Khimayah (Jurnal Kesehatan Masyarakat (Undip), 2015)
Lodoyong village is one of the villages in Ambarawa Semarang Regency with the number of dug wells are the most unhealthy at area community health centers of Ambarawa. Preliminary test results on one of groundwater samples showed levels of iron (Fe) is  4,2mg / l. It is more than the quality standar according to regulation of  ministry Health of Indonesia Number 492/Menkes/PER/IV/2010, so it is needs an efforts to overcome this with a cheap water treatment method and is applicable to zeolite media. This study is to determine the most efficient zeolite diameter to reduce iron (Fe) contens  of groundwater. This research is true experimental research, with the pretest-posttest with control group design.  The samples in this study is one of the groundwater in the Lodoyong villlage with Fe content exceeding standards. The results of this research show that the diameter of the zeolite that provides the greatest efficiency value in lowering levels of Fe ground water is the smallest diameter of zeolite (0,1-0,5 mm) with efficiency values by 86.73%. From these research can be concluded that the most efficient zeolit in reducing the Fe content is a zeolite with the smallest diameter (0,1-0,5mm) but, the zeolite has not been fully effective (effective approach) cause it just can lower Fe content up to 0,31 m g/l.